Answer:
1) y = tan(xlnx-x+tan⁻¹(3) + 1)
2) [tex]tan^{-1}y=2(1+x^3)^{\frac{3}{2}}+ tan^{-1}(3) - 2[/tex]
Step-by-step explanation:
1) y' = ln(x)(1 + y²), y(1) = 3 Ans y= tan(x lnx-x+1+tan⁻¹(3))
solution:
y' = ln(x)(1 + y²)
[tex]\frac{\mathrm{d} y}{\mathrm{d} x}= lnx\ (1+y^2)[/tex]
[tex]\frac{dy}{1+y^2}={lnx}{dx}\\\int\frac{dy}{1+y^2}=\int \{lnx}dx\\tan^{-1}y=xlnx-x+c[/tex]
using condition y(1) = 3
tan⁻¹(3)=-1+c
c = tan⁻¹(3) + 1
now,
tan⁻¹(y)=xlnx-x+tan⁻¹(3) + 1
y = tan(xlnx-x+tan⁻¹(3) + 1)
2) y' = 9x² √(1 + x)³ (1 + y²), y(0) = 3
[tex]\frac{\mathrm{d} y}{\mathrm{d} x}=9x^2\sqrt{1+x^3}(1+y^2)[/tex]
[tex]\dfrac{dy}{1+y^2} = 9x^2\sqrt{1+x^3}\\\int\dfrac{dy}{1+y^2} = \int9x^2\sqrt{1+x^3}\\ tan^{-1}y= \int9x^2\sqrt{1+x^3}[/tex]
let 1+x³=u [tex]{u}'= 3x^2[/tex]
[tex]tan^{-1}y=\int 3\sqrt{u}du\\tan^{-1}y=2u^{\frac{3}{2}}[/tex]
inserting value of 'u' in equation above
[tex]tan^{-1}y=2(1+x^3)^{\frac{3}{2}}+c[/tex]
inserting value y(0) = 3
c = tan⁻¹(3) - 2
[tex]tan^{-1}y=2(1+x^3)^{\frac{3}{2}}+ tan^{-1}(3) - 2[/tex]